Effect of Packaging Materials and Ethylene Absorbent on Shelf Life of Bell Pepper - Kadam, Dattatreya M; Singh, Jarnail (Journal of Agricultural Engineering, 2006)
An ethylene absorbent flush storage structure was developed using a plastic container and experiment was carried out to study the effect of ethylene absorbent (3% KMnO4 solution) and different packaging materials (open, jute and HOPE) on shelf life of bell pepper. Physico-chemical properties such as physiological loss in weight, moisture content, size, bulk density, firmness, total soluble solids, ascorbic acid, colour, and spoilage of bell pepper were studied with respect to packaging material inside the ethylene absorbent flush storage. The ambient temperature and RH during the storage period varied from 17 to 32Â°C and 74 to 95.5%, respectively. Fresh bell pepper had 128.38 mg/100 g of ascorbic acid and 90-95% moisture content on wet basis (w.b.). The quality of the bell pepper was evaluated based on the spoilage, shrinkage and change in colour. Minimum physiological loss in weight was 3.45% in open samples, moisture loss was 30.81 %, decrease in size was 2.38% and minimum decrease in ascorbic acid (17.96%) and change in shape was observed injute bag samples after 24 days of storage period inside the ethylene absorbent flush storage. Maximum increase in bulk density was 12.33% in HDPE bag after 12 days of storage. TSS increased at initial stages and decreased at later stage. The spoilage showed increasing trend throughout storage period irrespective of packaging materials. An ethylene absorbent flush storage with three percentage of KMnO4 solution increased the shelf life of bell pepper up to 12 days in HOPE packed samples and 24 days in open and jute bag samples.